Incorporação do resíduo catalítico do refino de petróleo em compósitos cimentícios - Will, Ramon (2022)
The fluidized bed catalytic cracking units seek to improve the efficiency of oil refining to produce lighter compounds with greater added value, using zeolite-based catalysts. The result of this process is the generation of an equilibrium catalyst (Ecat), which has world production around 400,000 ton/year, making it a problem for oil refineries. Ecat is basically composed of silica and alumina, which give it the possibility of being used as a pozzolanic material in cementitious matrices. In this context, the objective of this research was to evaluate the technical feasibility of partial replacement of cement by Ecat in cementitious composites, with contents of 5, 10, 15 and 20%. For this, a theoretical-experimental research was carried out, through a bibliographic review and, later, characterization of the material through the tests of Pozzolanic Activity Index (PAI), X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), X-Ray Fluorescence Spectrometry (XRF), specific mass and laser granulometry. Then, an analysis was carried out on the incorporation of Ecat in cementitious composites, through tests in the fresh and hardened state, evaluating the consistency, compressive strength, tensile strength by diametral compression, dynamic modulus of elasticity and water absorption by immersion and capillarity. Finally, a comparison was made of the results obtained experimentally with the reference sample, as well as the theoretical and experimental values found in the literature, verifying if the cementitious composite has potential use in the production of cementitious artifacts for civil construction. With the results, it was found that Ecat is mainly composed of SiO2 and Al2O3, with particle sizes ranging from 3.15 µm to 52.4 µm, BET specific surface of 44.49 g/cm³ and specific mass of 2.64 g/cm³. The mineralogical analysis identified an amorphous halo and the mineral faujasite as the main component. Ecat presented IAP with lime of 142%, performance index with Portland cement of 120% and calcium hydroxide fixation of 794 mg Ca(OH)2/g, all values above the minimum necessary to be considered as pozzolanic material. It can be concluded that the Ecat evaluated in this research has adequate pozzolanic activity, and can be used in its raw form in partial replacement of Portland cement and cementitious matrices.